Seleksi Penerimaan KIP Mahasiswa Menggunakan Weighted Aggregated Sum Product Assesment - Rio, Rio; Fadli, Muhamad (Journal of Information System Research (JOSH), 2024)
Indonesia Smart Card or known as KIP Lecture, is a college education assistance provided with the aim of exempting college entrance selection registration and tuition fees or education. This program is a government program that aims to help students who want to continue their education but are constrained by costs. However, to get a scholarship, you must fulfill the requirements in accordance with the provisions on each campus. One of the universities that has the opportunity to get a KIP Lecture quota is PGRI Silampari University, with a limited number of KIP quotas, the University tries to strictly select students who are declared eligible to receive the scholarship. Therefore, a decision support system is needed that can provide input in the form of the best value to the KIP manager, to select which students are declared eligible to receive this assistance. By utilizing the WASPAS Method, it is hoped that it can provide the best results and can help the PGRI University Lecture KIP manager in determining students who are eligible and not eligible to receive Lecture KIP assistance objectively. The results of this study are in the form of a ranking of scores that have been normalized by the WASPAS method. The student is M2 on behalf of Sugi with a value of 13.78443387, M5 student on behalf of Vienna with a value of 11.64127542 getting a rank 2, M3 student on behalf of Tejo getting a value of 11.64127542 getting a rank 3. The three students with the highest scores who are included in the rank 1, rank 2, rank 3 are declared eligible to receive the KIP Lecture scholarship.